Psychedelics as a Treatment for Alzheimer’s Disease Dementia - Vann Jones, Simon Andrew; O’Kelly, Allison (Frontiers in Synaptic Neuroscience, 2020)
Abstract Currently there are no disease-modifying treatments for Alzheimer’s disease or any other dementia subtype. The renaissance in psychedelic research in recent years, in particular studies involving psilocybin and lysergic acid diethylamide (LSD), coupled with anecdotal reports of cognitive benefits from microdosing, suggests that they may have a therapeutic role in a range of psychiatric and neurological conditions due to their potential to stimulate neurogenesis, provoke neuroplastic changes and reduce neuroinflammation. This inevitably makes them interesting candidates for therapeutics in dementia. This paper will look at the basic science and current clinical evidence for the role of psychedelics in treating dementia, with a focus on the classical psychedelics LSD and Psilocybin and Alzheimer’s disease.